A Classical Survey On Rotundity of Norms in Banach Spaces - Wanjara, Amos Otieno (Universitas Brawijaya, 2024)
The study on rotundity of norms in Banach spaces is of interest to many mathematicians. This is because rotundity properties are strongly applicable in many branches of Mathematics including but not restricted to functional analysis and topology. Some of the properties include: Rotund, Locally Uniformly Rotund, Uniformly Rotund in every direction, Uniformly Rotund in Weakly Compact sets of direction among others. In this paper, we give a survey of the standard results that will really revolutionize the study and research on rotundity of norms in the fields of functional analysis and topology among others.